2017
DOI: 10.1111/acer.13488
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Levels of mGlu2 Receptors within the Prelimbic Cortex Are Not Associated with Elevated Glutamate Transmission or High Alcohol Drinking

Abstract: Background A Grm2 cys407* stop codon mutation, which results in a loss of the metabotropic glutamate 2 (mGlu2) receptor protein, was identified as being associated with high alcohol drinking by alcohol preferring (P) rats. The objectives of the current study were to characterize the effects of reduced levels of mGlu2 receptors on glutamate transmission and alcohol drinking. Methods Quantitative no-net-flux microdialysis was used to test the hypothesis that basal extracellular glutamate levels in the prelimbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…These studies suggest that within the NAC, mGlu 2/3 function in the shell subregion may be particularly sensitive to the effects of ethanol exposure. In addition, drinking-induced decreases in mGlu 2/3 autoreceptor function have also been observed in the VTA . In contrast to these findings in the mesocorticolimbic system, enhanced sensitivity to mGlu 2/3 agonists has been observed in the CEA and BNST of ethanol-dependent rats .…”
Section: Basic Mglu Receptor Physiologymentioning
confidence: 90%
See 1 more Smart Citation
“…These studies suggest that within the NAC, mGlu 2/3 function in the shell subregion may be particularly sensitive to the effects of ethanol exposure. In addition, drinking-induced decreases in mGlu 2/3 autoreceptor function have also been observed in the VTA . In contrast to these findings in the mesocorticolimbic system, enhanced sensitivity to mGlu 2/3 agonists has been observed in the CEA and BNST of ethanol-dependent rats .…”
Section: Basic Mglu Receptor Physiologymentioning
confidence: 90%
“…In addition, drinking-induced decreases in mGlu 2/3 autoreceptor function have also been observed in the VTA. 119 In contrast to these findings in the mesocorticolimbic system, enhanced sensitivity to mGlu 2/3 agonists has been observed in the CEA and BNST of ethanol-dependent rats. 120 Interestingly, these findings were associated with enhanced behavioral sensitivity to mGlu 2/3 agonists in their ability to reduce ethanol-motivated behavior.…”
Section: Acs Chemical Neurosciencementioning
confidence: 99%
“…Reduced expression in the infralimbic cortex has been associated with increased vulnerability to cueinduced reinstatement of alcohol seeking (Meinhardt et al, 2013). Conversely, efforts to identify a role for prelimbic cortex mGlu 2 in voluntary drinking demonstrated that 40% knockdown of mGlu 2 from this region was insufficient to increase drinking behavior in rats (Ding et al, 2017). Further studies focused on cortical regions projecting to the DLS will be necessary to pinpoint the affected cortical or thalamic afferents and to determine the behavioral ramifications of disinhibition of affected striatal inputs.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, it has been reported that ethanol-dependent rats have decreased PFC GRM2 mRNA levels and mGlu 2/3 autoreceptor function in the NAc shell compared with control rats ( Meinhardt et al, 2013 ). In addition, drinking-induced decreases in mGlu 2/3 autoreceptor function have also been observed in the VTA ( Ding et al, 2017 ). Alternatively, enhanced physiologic and behavioral sensitivity to mGlu 2/3 agonists is observed in the central nucleus of the amygdala and bed nucleus of stria terminalis of ethanol-dependent rats ( Kufahl et al, 2011 ).…”
Section: Potential Of Allosteric Modulators Of Metabotropic Glutamate...mentioning
confidence: 99%